2017
DOI: 10.2298/tsci17s2473m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steam injection on nox emissions and performance of a single cylinder diesel engine fuelled with soy methyl ester

Abstract: Biodiesel attracts most of the researchers and automotive industries in recent years as an alternative fuel for diesel engines, because of its better lubricity property, higher cetane number, and less greenhouse gas emissions. The use of bio diesel leads to reduction in hydro carbons, carbon monoxide, and particulate matter, but increase in NO x emissions. Increase in biodiesel blends in standard diesel leads to increase in NO x emission. In this study, an attempt is made to reduce the NO x emissions of a dies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…The NO x emissions increased compared to diesel when blended fuel and biodiesel were used except for the fact that there was a slight decrease in blended fuel compared to diesel at 10.2 kW. In addition, this increase became more apparent with the increase in the load, as found in other studies [21]. For example, under 3.6 kW load conditions, NO x turned out to be 1% and 5.5% more in use of blended fuel and biodiesel according to diesel, respectively, while the change in NO x was found at the rate of 1.3-0.5% and 9.2-4.5% for blended fuel and biodiesel when the load was increased to 7 kW and 10.2 kW, respectively.…”
Section: Exhaust Emissionssupporting
confidence: 65%
“…The NO x emissions increased compared to diesel when blended fuel and biodiesel were used except for the fact that there was a slight decrease in blended fuel compared to diesel at 10.2 kW. In addition, this increase became more apparent with the increase in the load, as found in other studies [21]. For example, under 3.6 kW load conditions, NO x turned out to be 1% and 5.5% more in use of blended fuel and biodiesel according to diesel, respectively, while the change in NO x was found at the rate of 1.3-0.5% and 9.2-4.5% for blended fuel and biodiesel when the load was increased to 7 kW and 10.2 kW, respectively.…”
Section: Exhaust Emissionssupporting
confidence: 65%
“…According to a previous work presented by the authors the numerical code has been tuned in order to validate successfully CO, CO 2 , and O 2 concentrations. It has been shown that, for the five loads, measured values of [O 2 ], [CO] and [CO 2 ] at the exhaust valve opening lies perfectly with those obtained by kiva3v2[19]. Thus, the tabulated chemistry used led to a suitable prediction of O 2 , CO and CO 2 concentrations in the exhaust.…”
supporting
confidence: 54%
“…2-Maximal in-cylinder pressure rather than temperature as proposed in [19]. In fact, maximum value of the averaged in-cylinder pressure, like temperature, is a thermodynamic function but much easier to measure in addition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations